Nonlinear Failure Analysis of Critical Area of Transmission Towers Based on the Continuum Damage Theory - Nailong Zhang; Jie Chen; Chao Gao; Xiao Tan; Hongze Li (International Transactions on Electrical Energy Systems)
Transmission towers serve as crucial safety pillars within the power transmission system, and their damage can lead to severe consequences. The structural failure of a tower undergoes a process from the initiation of local damage to overall failure, emphasizing the importance of conducting detailed local safety research. This paper introduces a nonlinear damage analysis method rooted in the continuous damage theory, specifically designed for critical areas of transmission towers. A material subroutine for elastic-plastic-damage constitutive equations is developed using commercial software, and thorough verification ensures the accuracy of both the subroutine and the algorithm. The proposed algorithm is then applied to analyze the damage in critical areas of a tower, simulating the plasticity-damage coupling evolution of the main leg during the collapse of the transmission tower. Regarding the treatment of bolt connections in the local model, it indicates that there is a small difference between the contact model and the rigid-joint model results. Taking computational efficiency into consideration, it is recommended to employ rigid-joint model to simulate the evolution of damage. The presented example illustrates damage occurring on the outer side of the main leg, ultimately leading to lateral damage under the combined influence of bending and torsion. This research offers a novel method for investigating the failure mechanisms of transmission towers under extreme weather conditions and proposes precise reinforcement strategies.